CHALLENGES FACED BY DESIGN ENGINEERS WHEN CONSIDERING MANUFACTURING IN DESIGN – AN INTERVIEW STUDY. (May 2020) - Doellken, M.; Zimmerer, C.; Matthiesen, S.
Abstract: The consideration of manufacturing in design is still a challenge for design engineers. This paper presents the results of an interview study, conducted with 15 participants. 4 challenges are identified in this study: Manufacturing-specific knowledge is mostly not sufficient. The design of manufacturing-oriented concepts in terms of costs is difficult. The feasibility of manufacturing is not assessed. The dimension of cost drivers is unknown, hindering optimisation in early stages of design. Based on these results the need for further research emerges regarding the impact of these challenges.